Use of Mustard oil as an alternative and renewable substitute of Fossil diesel - Hasib, Z.M.; Rahman, K.A.; Alam, M.M. (BRAC University, 2012)
Energy is the prerequisite for modern civilization. Fossil fuel is still the main source of energy. But the endless consumption of fossil fuel has brought its reserve about to an end. As a result, fuel prices are growing as a consequence of spiraling demand and diminishing supply. So we are always in search of alternative and cost effective fuels, to meet our need. Diesel engines are more efficient and costeffective than other engines. So diesel engines have versatile uses (i.e. automobiles, irrigation, power plants etc.). That is why; consumption of diesel fuel is much higher than other gasoline fuels. This paper estimates the feasibility of mustard oil as an alternative fuel for diesel engine. Mustard is a renewable plant, widely growing in almost everywhere in Bangladesh. In this study, mustard oil is converted to bio-diesel by well known trans-esterification reaction. Bio-diesel has different fuel properties than diesel fuel. So other than modification of the engine or the fuel supply system, blends of bio-diesel (i.e. B20, B30, B50 etc,) has been used. Finally, a comparison of engine performance for different blends of bio-diesel has been carried out to choose the correct blend for different operating conditions.